KETERTIBAN YANG ADIL VERSUS KETIDAKADILAN: BEBAN SOSIAL-EKONOMI YANG HISTORIS DARI HUKUM - Kusumohamidjojo, Budiono (Faculty of Law, Parahyangan Catholic University, 2016)
This paper is based on a two decade observation on the dilemma of order and justice, leading to an attempt to analyze the social-economic factors underlying the historical roots of injustice. On its course it attempted to take lessons from historically proven axioms provided by certain heavy weight thinkers. While trying to make the best out of those axioms, the analysis could not ignore the hard facts of the daily life of the billions of people suffering from unending injustice in most parts of the world, in the rich and let alone in the poor parts of it. Neither could it escape from criticizing the ubiquitous mess in the justice system, almost universally. Although the overall problem of injustice does not seem to provide much hope for a better life of the people at large, the conclusion of this paper tried to distant away from a pessimistic stance and instead proposed an agenda for those who may concern to be carried out. This paper contains forethoughts of a book in the making regarding basically the same problem. Keywords:history, authority, rationality, law, order, equality, justice